2016
DOI: 10.1099/jgv.0.000554
|View full text |Cite
|
Sign up to set email alerts
|

Feral swine virome is dominated by single-stranded DNA viruses and contains a novel Orthopneumovirus which circulates both in feral and domestic swine

Abstract: Feral swine are known reservoirs for various pathogens that can adversely affect domestic animals. To assess the viral ecology of feral swine in the USA, metagenomic sequencing was performed on 100 pooled nasal swabs. The virome was dominated by small, ssDNA viruses belonging to the families Circoviridae, Anelloviridae and Parvovirinae. Only four RNA viruses were identified: porcine kobuvirus, porcine sapelovirus, atypical porcine pestivirus and a novel Orthopneumovirus, provisionally named swine orthopneumovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 29 publications
1
22
1
Order By: Relevance
“…Torque teno virus (Anelloviridae) was the most commonly detected virus (73%), PCV2 was identified in 13% of the samples. Only four RNA viruses were identified: kobuvirus, sapelovirus, pestivirus and an orthopneumovirus [17]. This is in contrast to previous studies of the faecal virome which were dominated by RNA viruses [6,7].…”
Section: The Porcine Viromecontrasting
confidence: 84%
See 1 more Smart Citation
“…Torque teno virus (Anelloviridae) was the most commonly detected virus (73%), PCV2 was identified in 13% of the samples. Only four RNA viruses were identified: kobuvirus, sapelovirus, pestivirus and an orthopneumovirus [17]. This is in contrast to previous studies of the faecal virome which were dominated by RNA viruses [6,7].…”
Section: The Porcine Viromecontrasting
confidence: 84%
“…When the virome of feral swine (wild boars) in the US was analysed, a total of 16 different viruses were identified [17]. Mainly single stranded DNA viruses were detected including Circoviridae, Anelloviridae and Parvovirinae.…”
Section: The Porcine Viromementioning
confidence: 99%
“…Members of the Human orthopneumovirus species are divided into the co-circulating subgroups A1, A2, B1 and B2. Viruses closely related to murine orthopneumovirus have been isolated from dogs and pigs [6].…”
Section: Taxonomymentioning
confidence: 99%
“…Seven different viruses have been identified in several animal species as belonging to this family: avian metapneumovirus (AMPV) and human metapneumovirus (HMPV) for the Metapneumovirus genus, bovine respiratory syncytial virus (BRSV), ovine respiratory syncytial virus (ORV), human respiratory syncytial virus (HRSV), pneumonia virus of mice (PVM), and canine pneumovirus (CPV) for the Orthopneumovirus genus. More recently, an eighth pneumovirus was identified by metagenomic sequencing of pooled nasal swabs in feral swine in the USA [ 4 ]. This newly identified Orthopneumovirus shows 93% and 91% protein identities with PVM and CPV, respectively, and was named swine Orthopneumovirus (SOV).…”
Section: Introductionmentioning
confidence: 99%
“…This newly identified Orthopneumovirus shows 93% and 91% protein identities with PVM and CPV, respectively, and was named swine Orthopneumovirus (SOV). Since no specific enzyme-linked immunosorbent assay (ELISA) is available for SOV, based on the close genetic relationship between PVM and SOV Hause et al used a commercial ELISA to detect antibodies to PVM and found that 31% of the analysed feral swine sera were antibody positive [ 4 ]. Finally, analyses by the same PVM ELISA of sera from different American farms revealed that sera were 33% to 93% positive, dependent on the farms, and confirmed that SOV is also present in domestic swine.…”
Section: Introductionmentioning
confidence: 99%